2011
DOI: 10.1097/cmr.0b013e328343a1d6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of receptor tyrosine kinase activation in human melanomas reveals autocrine signaling through IGF-1R

Abstract: Melanomas depend on autocrine signals for proliferation and survival; however, no systematic screen of known RTKs has been performed to identify which autocrine signaling pathways are activated in melanoma. Here we performed a comprehensive analysis of 42 receptor tyrosine kinases (RTKs) in 6 individual human melanoma tumor specimens as well as 17 melanoma cell lines, some of which were derived from the tumor specimens. We identified 5 RTKs that were active in almost every one of the melanoma tissue specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 43 publications
4
39
0
Order By: Relevance
“…Melanoma cell lines with BRAF V600E mutations showed relatively little basal RTK signaling, with the exceptions of ephrin A4 and one cell line (WM9) with EGFR/ERBB2/ERBB3 activity (Figure 1A). The analysis detailed here differs significantly from previous studies of RTK activity in melanoma cell lines in utilizing mass spectrometry to give precise, quantitative readouts on specific phosphorylation sites (Figure 1A) (7, 8). In agreement with previously published studies, we noted basal tyrosine phosphorylation of Axl at Y702 in all of the NRAS -mutant melanoma cell lines that was lacking in those that were BRAF -mutant (12).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Melanoma cell lines with BRAF V600E mutations showed relatively little basal RTK signaling, with the exceptions of ephrin A4 and one cell line (WM9) with EGFR/ERBB2/ERBB3 activity (Figure 1A). The analysis detailed here differs significantly from previous studies of RTK activity in melanoma cell lines in utilizing mass spectrometry to give precise, quantitative readouts on specific phosphorylation sites (Figure 1A) (7, 8). In agreement with previously published studies, we noted basal tyrosine phosphorylation of Axl at Y702 in all of the NRAS -mutant melanoma cell lines that was lacking in those that were BRAF -mutant (12).…”
Section: Resultsmentioning
confidence: 81%
“…Melanoma cell lines and tumor specimens express a large number of cell surface receptor tyrosine kinases (RTKs), all with the potential to drive cell growth and survival (7, 8). There is some preclinical evidence that multi-targeted kinase inhibitors, such as RAF-265, may have in vivo activity against patient-derived BRAF wild-type melanoma xenografts, including those with NRAS Q61R mutations (9).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of cancer models indicate that Ron is highly expressed in the epithelial cells of the tumor [16]. In addition to the numerous cancers in which Ron overexpression has been identified, recent reports indicate that Ron is also upregulated in human gliomas [17], melanoma [18] and Merkel cell carcinoma [19]. Merkel cell carcinoma is a neuroendocrine tumor of the skin; the addition of these 3 cancer subtypes suggest Ron is also playing a role in both neurological and skin cancers, expanding its role to most known cancer subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the results revealed that in MDA-MB-231 cells only a few RTKs are active. In other human cell lines that we have examined, such as melanomas, we found a different subset of activated RTKs [6], demonstrating the responsiveness and validity of the assay. Combination treatment of peroxyvanadate plus SLO did not reveal differences in RTK activation relative to control cells treated with peroxyvanadate alone (Figure 2B).…”
Section: Resultsmentioning
confidence: 70%